Acute Effect of a Dietary Multi-Ingredient Nootropic as a Cognitive Enhancer in Young Healthy Adults: A Randomized, Triple-Blinded, Placebo-Controlled, Crossover Trial - Medrano, María; Molina-Hidalgo, Cristina; Alcantara, Juan M. A.; Ruiz, Jonatan R.; Jurado-Fasoli, Lucas (Frontiers in Nutrition, 2022)
Aim: To study the acute effect of a dietary multi-ingredient nootropic on cognitive performance in young healthy adults. We also analyzed the influence of the dietary multi-ingredient nootropic on emotional state, heart rate (HR), and heart rate variability (HRV). Methods: This is a randomized, triple-blinded, placebo-controlled, crossover trial. 26 young healthy adults (50% women; 24.9±3.3 years old) ingested 10g of a dietary multi-ingredient nootropic [Evo-Gamers®; Harrison Sport Nutrition (HSN), Granada, Spain] or placebo (maltodextrin) in a randomized order (clinicaltrials.gov No. NCT04790188). After 30 min of the ingestion, participants performed a battery of cognitive performance tests to measure processing speed, inhibitory control, working memory, cognitive flexibility, creativity, and verbal fluency. Emotional status was assessed through questionnaires and HR and HRV were measured using a heart rate monitor. Results: In comparison with placebo, the acute ingestion of the nootropic showed a significantly better response time in several cognitive tests (i.e., processing speed, inhibitory control, spatial working memory, and cognitive flexibility, all P<0.05 and effect size range of 0.4-0.6). It also displayed a higher accuracy in the processing speed, in the inhibitory control and cognitive flexibility tests (all P<0.05; effect size ranged from 0.4 to 0.6). Furthermore, the nootropic showed a higher creativity and positive emotions, lower sadness-depression emotions, whereas HR and HRV remained similar between placebo vs nootropic conditions. However, there were no differences between the nootropic and placebo in verbal fluency, motivation, or anxiety (all P>0.05). Conclusion: An acute ingestion of a dietary multi-ingredient nootropic enhances cognitive performance in comparison with placebo without negatively influencing HR or HRV in young healthy adults.